2020
DOI: 10.2174/1389201021666200611112755
|View full text |Cite
|
Sign up to set email alerts
|

Novel Therapeutic Approaches and Targets for the Treatment of Atopic Dermatitis

Abstract: Background: Atopic Dermatitis is one of the most common inflammatory skin diseases , with an estimated prevalence of 2.1-4.9% in adults. Recently, advances in Atopic Dermatitis understanding have highlighted the role of an inappropriate Th2 cells activation as principally involved in its pathogenesis. Other immune pathways seem to play a key role in the complex Atopic Dermatitis pathophysiology. The anti-IL-4/IL-13 was the first monoclonal antibody approved for the treatment of moderate to severe atopic derma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…On the other hand, considering that not all patients with AD display filaggrin mutations, a combination of primary and secondary barrier defects underlies the disease process. Thus, the inflammation in AD patients, predominantly characterized by a strong and inappropriate Th2 cell activation [68], affects the integrity of the epidermal barrier on multiple levels. Secondary factors adversely affecting the epidermal barrier integrity are predominant in the pathogenesis of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, considering that not all patients with AD display filaggrin mutations, a combination of primary and secondary barrier defects underlies the disease process. Thus, the inflammation in AD patients, predominantly characterized by a strong and inappropriate Th2 cell activation [68], affects the integrity of the epidermal barrier on multiple levels. Secondary factors adversely affecting the epidermal barrier integrity are predominant in the pathogenesis of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…A phase 3 study demonstrated improvements in pruritus, sleep loss and QoL at week 16, confirming the importance of IL‐31 in itch mediation 255 . Conversely, agents that target Th17/IL‐23 (ustekinumab), 256 IL‐17A (secukinumab), 257 IL‐17A and IL‐17F (bimekizumab) and IL‐22 (fezakinumab) have had limited success, ruling out these cytokines as key players in AD 1,202,258 …”
Section: Treatmentmentioning
confidence: 99%
“…With such information, it will be possible to consider personalized and selective drug strategies (PESCITELLI et al, 2021), minimizing the occurrence of extensive side effects and optimizing therapeutic responses.…”
Section: Phenotype Based Therapymentioning
confidence: 99%